Allelic and genotypic analysis of the ACE I/D polymorphism for the possible prediction of COVID-19-related mortality and morbidity in Jordanian Arabs - Laith Naser AL-Eitan; Saif Zuhair Alahmad (Journal of Biosafety and Biosecurity, 2023)
The coronavirus disease 2019 (COVID-19) pandemic has rapidly spread worldwide, posing a global medical concern. This novel RNA virus enters cells by binding to angiotensin-converting enzyme II (ACE2) receptors. Additionally, ACE (ACE1) polymorphisms can influence ACE2 activity and consequently affect COVID-19 patient outcomes. This study aimed to determine the genotypic and allelic frequencies of the insertion/deletion polymorphism (ACE I/D; rs4646994) in the ACE gene among Arab Jordanians. Moreover, we investigated if there is a genetic association between the allele and genotype frequencies of the rs4646994 polymorphism with respect to gender. We isolated DNA from approximately 525 blood samples for genotyping of the ACE I/D polymorphism, which was performed using a 3% agarose gel mixed with ethidium bromide. Our findings indicated a significantly higher distribution of the D allele (66%) compared with the I allele (34%) in the Jordanian population. Moreover, the DD genotype (42%) was more prevalent than the II genotype (11%). We observed a significant association in the genotypic frequency, but not the allelic frequency, between males and females. Our research has revealed the potential role of the ACE I/D variant in the increased COVID-19 morbidity and mortality rates in the Jordanian population.